A comparative study of the similarities and differences between âassistingâ and âcausingâ within two rules: the prohibition of âassistance with sinsâ and âcausationâ - Ã˜Â¢Ã™Â‡Ã™Â†ÃšÂ¯Ã˜Â±Ã›ÂŒ, Ã˜Â§Ã˜ÂÃ˜Â³Ã˜Â§Ã™Â†; Ã™Â…Ã™Â‡Ã˜Â¯Ã™ÂˆÃ›ÂŒ, Ã˜Â§Ã˜ÂµÃ˜ÂºÃ˜Â± Ã˜Â¢Ã™Â‚Ã˜Â§ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Assistance with sinsâ and âcausationâ are two important jurisprudential rules with crucial implications. âAssistingâ and âcausingâ as derived from those rules have a lot in common. At the same time, what their differences are seems to be an important issue. The subtle differences between the two sometimes lead to confused identifications and examples of each might be mistaken with the other. We have examined the differences between the two within five areas. These are as follows: discussion of centrality or non-centrality of each, sobriety of the assistant as condition or non-condition, intention as a condition for the truth of the two issues, inclusion of the two rules in the context of abandonment or non-abandonment (continuity), and expression of obligatory and situational rulings on âassistingâ and âcausing.â